The Impact of Hybrid Working on Employee Performance : A Study on Startup Companies in Surabaya - Sumiati Sumiati (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
This study aims to analyze the effect of Hybrid Working and Work-Life Balance on Employee Performance in startup companies in Surabaya. In addition, this study also explores the role of additional variables (YM) in the relationship. The approach used in this study is quantitative with survey method. Data was collected through questionnaires from 100 respondents who are employees at various startups in Surabaya that implement a hybrid working system. Data analysis was conducted using multiple linear regression method with two test models (Model 1 without additional variables and Model 2 with additional variable YM).The results showed that in Model 1, Hybrid Working and Work-Life Balance had a positive and significant effect on Employee Performance (p-value <0.05). This model has an R Square of 44.2%, which means that the two variables explain 44.2% of the variation in Employee Performance. However, in Model 2, after adding the YM variable, the effect of Hybrid Working and Work-Life Balance on Employee Performance became insignificant (p-value > 0.05). Nonetheless, the overall model remains significant (F = 26,081, p = 0.000) with an increase in the R Square value to 44.9%. Hybrid Working and Work-Life Balance have a significant impact on Employee Performance, but this relationship may change when other variables are included in the model.